Hydrocortisone 21-hemisuccinate did not prevent exogenous GAPDH-induced apoptosis in human neuroblastoma cells - Lazarev, Vladimir F. (Data Brief, 2018)
These data are related to our paper “GAPDH-targeted therapy – a new approach for secondary damage after traumatic brain injury on rats” (Lazarev et al., In press), in which we explore the role of exogenous GAPDH in traumatic brain injury-induced neuron death, and the therapeutic application of small molecules that bind to the enzyme. The current article demonstrates the induction of apoptosis by exogenous GAPDH and the effectiveness of the hydrocortisone derivative for suppressing the pathogenic action of the enzyme.